2007
DOI: 10.1016/j.jacc.2006.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Eccentric Remodeling and Matrix Loss Are Mediated by Bradykinin and Precede Cardiomyocyte Elongation in Rats With Volume Overload

Abstract: Immediately after ACF induction, eccentric LV remodeling is mediated by interstitial collagen loss without cardiomyocyte elongation. Acute BK2R blockade prevents eccentric LV remodeling and improves function. Chronic ACE inhibition does not prevent eccentric LV remodeling or improve function. These findings suggest that ACE inhibitor-mediated increase in LV BK exacerbates matrix loss and explains why ACE inhibition is ineffective in VO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
159
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(172 citation statements)
references
References 23 publications
11
159
2
Order By: Relevance
“…A significant increase in myocyte diameter, however, was found in the T2DN mtFHH rats in comparison with T2DN mtWistar . This result coincides with the increase in LV dimensions observed in echocardiographic analysis and is consistent with previous findings that increased cardiomyocyte length is associated with eccentric left ventricular remodeling and dilation (19).Mitochondrial Biogenesis-Slides from two transmission electron microscopy nonserial sections at ϫ8000 and ϫ29,000 magnification were analyzed for mitochondrial number, distribution, and morphology (Fig. 3).…”
supporting
confidence: 90%
“…A significant increase in myocyte diameter, however, was found in the T2DN mtFHH rats in comparison with T2DN mtWistar . This result coincides with the increase in LV dimensions observed in echocardiographic analysis and is consistent with previous findings that increased cardiomyocyte length is associated with eccentric left ventricular remodeling and dilation (19).Mitochondrial Biogenesis-Slides from two transmission electron microscopy nonserial sections at ϫ8000 and ϫ29,000 magnification were analyzed for mitochondrial number, distribution, and morphology (Fig. 3).…”
supporting
confidence: 90%
“…Ruzicka et al used this model for describing renin-angiotensin system and effects of angiotensin converting enzyme inhibitors in situation of volume overload (Ruzicka et al, 1993). Ryan et al described remodeling process induced by bradykinin (Ryan et al, 2007). Study of Hatt et al (1979) is closest to our morphological approach.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished systemic perfusion leads to redistribution of cardiac output and neurohumoral activation. When compensatory mechanisms become inadequate, overt heart failure (HF) develops (Hood et al, 1968) in a way similar to other models of LV hypertrophy-HF transition (Hatt et al, 1979;Legault et al, 1990;Ruzicka et al, 1993;Ryan et al, 2007).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Pharmacologic inhibition studies suggested that MMP activation is directly implicated in dilative remodeling of the volume-overloaded ventricle (117), but the mechanisms responsible for the distinct cell biological changes and matrix alterations in volume overload remain poorly understood. Bradykinin receptor signaling has been implicated in matrix loss associated with volume overload (118), but the links between specific mechanical stimuli and myocardial cell activation are understudied. The limited data on the matricellular protein profile in volume-overloaded hearts are not accompanied by systematic investigations of the potential role of these proteins.…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%